Validation of the English Version of the HeartQoL Health-Related Quality of Life Questionnaire in Patients With Coronary Heart Disease. Issue 2 (March 2018) - Oldridge, Neil; Cho, Chris; Thomas, Randal; Low, Murray; Höfer, Stefan
Abstract : Purpose: The aim of this study was to validate the English version of the HeartQoL health-related quality of life questionnaire for use in patients with angina or myocardial infarction. Methods: Patients living in the United States and referred, either for percutaneous coronary intervention or to cardiac rehabilitation, completed the HeartQoL, the Short Form-36 Health Survey, and the Hospital Anxiety and Depression Scale at baseline and 3-months later. The data were analyzed for validity, reliability, and responsiveness. Results: Patients (n = 313 with angina and n = 97 with myocardial infarction) who were referred either for percutaneous coronary intervention (n = 164) or to cardiac rehabilitation (n = 246) completed baseline questionnaires. Patients with angina had significantly lower HeartQoL scores (poorer health-related quality of life) compared with patients with myocardial infarction. Exploratory factor analysis largely supported the 2-factor structure of the HeartQoL in both diagnoses, but further investigation is warranted. Internal consistency reliability was adequate, convergent validity correlations were significant, and discriminative validity was fully confirmed in patients with angina and largely confirmed in patients with myocardial infarction. Responsiveness was largely confirmed in patients who underwent percutaneous coronary intervention (n = 67) and those referred to cardiac rehabilitation (n = 167) with conventional statistical tests and clinically with the effect size, a standardized measure of change. Conclusions: The English HeartQoL health-related quality of life questionnaire is valid, reliable, and responsive in patients with angina and myocardial infarction allowing (1) assessment of baseline, (2) between-diagnosis comparisons, and (3) evaluation of change over time. Abstract : The English HeartQoL health-related quality-of-life (HRQL) questionnaire is valid, reliable, and responsive in patients with angina and myocardial infarction allowing (1) assessment of baseline HRQL, (2) between-diagnosis HRQL comparisons, and (3) evaluation of change over time.